The Atonement of Our Parent's Sin: Place-Based Narrative of Indonesia’ Drowning Muslim Community - Siti Aliyuna Pratisti; Zainal Abidin Bagir; Heddy Shri Ahimsa Putra; Michael S. Northcott (UIN Sunan Gunung Djati Bandung, 2023)
This article emphasised the local Muslim community's response to environmental change and explored how religious narratives play a significant role in shaping their action. Place-based narrative is employed as conceptual frame to scrutinise the community’s understanding of the drowning condition. As a case study, Pantai Bahagia Village in West Java is selected based on two criteria: (1) deemed as the fastest drowning area in the North Java Coast; and (2) the existing Muslim-based environmental activism initiated by local teachers in responding to environmental change. For method, qualitative case study is applied by conducting interviews, group discussions, and direct observation. Findings show that the local history of Pantai Bahagia interacts with a national political event in the 1960s that eventually triggers massive environmental change in the Beting area. Further analysis of the place-based narrative indicates that familiarity with religious expressions encourages ecological awareness in the local community and provides the basis for environmental activism.